Optimalisasi Strategi Digital Public Relations melalui TikTok dalam Membangun Branding Kuliner di Bali - I Gusti Putu Putra Artika; Ni Luh Yulyana Dewi (MANABIS: Jurnal Manajemen dan Bisnis, 2025)
The rapid development of Digital technology has transformed public communication and marketing strategies across various sectors, including the culinary industry. Social media platforms such as TikTok have become essential tools for business owners to strengthen their brand image and build engagement with audiences through creative and interactive visual content. This study aims to analyze the optimization of Digital Public Relations (PR) strategies through TikTok in developing culinary branding in Bali. The research employs a literature review approach by examining national and international scholarly articles published within the last five years that discuss Digital communication, public relations, and culinary branding strategies. Data were collected through a systematic search using relevant keywords across academic databases. The findings reveal that effective Digital PR strategies on TikTok consist of four main components: audience research, culturally based content planning, participatory two-way communication, and continuous evaluation supported by consumer trust. This approach enhances audience engagement and strengthens the brand image of Balinese culinary products as representations of local cultural identity. The study concludes that TikTok serves not only as a promotional platform but also as a Digital cultural communication space that connects traditional values with modern communication strategies in a sustainable manner.